Dampak pendidikan berbasis kompetensi terhadap peningkatan kognitif dan keterampilan klinis pada mahasiswa kebidanan - Annisa Karima Harda; Josi Noviani; Cindy Maharani Putri; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2026)
Midwifery education is increasingly shifting toward the implementation of Competency-Based Education (CBE), a transformative approach aimed at producing graduates with robust clinical and cognitive competencies by emphasizing measurable outcomes across cognitive, psychomotor, and affective domains. Understanding how the CBE model is implemented and the outcomes it yields is crucial for informing curriculum design, faculty development, and institutional readiness. This article aims to evaluate the impact of CBE on enhancing the clinical skills and cognitive development of midwifery students. A literature search was conducted across PubMed, Google Scholar, Scopus, and ScienceDirect databases using Boolean operators for keywords related to CBE and midwifery education. Studies were selected using the PRISMA method based on specific inclusion criteria, resulting in the identification of 13 relevant studies published between 2021 and 2026. The analysis indicates that CBE significantly improves students' clinical procedural skills, critical thinking abilities, and decision-making capabilities. Simulation-based approaches, problem-based learning, and structured assessments proved effective in supporting competency attainment. However, implementation barriers—such as resource limitations, a lack of faculty training, and institutional resistance—remain prevalent, particularly in resource-limited settings. CBE contributes positively to the development of clinical and cognitive competencies among midwifery students.